Issues of Prevention of Oculocardial Reflexes during Anesthesia in Pediatric Ophthalmology - S. Sh., Joniyev; M., Yuldashev (American Journal of Bioscience and Clinical Integrity, 2026)
This article presents a literature review dedicated to the issues of improving anesthesia in ophthalmic surgery for children, analyzing the unique anatomical, physiological, and behavioral characteristics of pediatric ophthalmosurgery. The primary focus is on the following challenges: maintaining intraocular pressure (IOP) stability, the oculocardiac reflex, the narrowness and propensity for collapse of airways, emergence agitation, sympathetic hyperreactivity, and the high metabolic rate in children. It is emphasized that these factors directly influence the quality and safety of general anesthesia. The review compares the advantages and limitations of volatile anesthetics such as sevoflurane (IOP elevation, emergence agitation) with the positive properties of propofol, ketamine, and particularly dexmedetomidine (IOP reduction, hemodynamic stability, agitation mitigation). Multimodal and opioid-sparing approaches, including dexmedetomidine-based combinations, are highlighted as promising directions in contemporary pediatric ophthalmic anesthesia.